Authentic Leadership and Organizational Effectiveness at Private Universities: The mediating effect of Virtuousness - Ahmad Nawaz; Fransisca Laij (International Journal of Digital Entrepreneurship and Business, 2021)
The purpose of this study is to investigate the relationship between authentic leadership, organizational Virtuousness, and departmental effectiveness at private universities in Jakarta. Two-stage sampling was undertaken in this study. In the first stage, a sample of 17 private universities was selected using a simple random sampling technique. In the second stage, faculty members were randomly contacted from the selected departments from sampled private universities to fill out the questionnaire for this study. Data was collected from the experienced faculty members of various departments of private universities and processed through the Structural Equation Modelling - PLS technique. This study finds that Authentic leadership plays a significant role in cultivating a virtuous environment in a private university department and enhances organizational effectiveness within the department of private universities. Furthermore, the findings propose that organizations must reinforce significant internal powers such as authentic leadership and organizational Virtuousness to improve their efficiency and effectiveness. Authentic leadership, as an upbeat leadership style, can nurture positive qualities in the company. The amplifying and buffering roles of organizational Virtuousness will contribute to the organization’s effectiveness. Limitations of the study were primarily because the focus was on relatively contemporary topics like authentic leadership and organizational Virtuousness, which are part of the evolving research areas. There is little information available, particularly in the context of Indonesian organizations. Secondly, the number of items in the original survey instrument was too large to be efficiently answered in one questionnaire; therefore, it was cut short to a more appropriate scale with experts’ assistance.